The Impact of the COVID-19 Pandemic on Families: Young People’s Experiences in Estonia - Kutsar, Dagmar; Kurvet-Käosaar, Leena (Frontiers in Sociology, 2021)
This article reflects the impacts of the COVID-19 pandemic on the everyday lives of children and their families in Estonia during the lockdown in spring 2020 and 2021. The data corpus is based on children’s diaries that were compiled during the first lockdown in 2020 for a collection at the Estonian Literary Museum and on a series of semi-structured interviews with children documenting their experiences during the lockdown in spring 2021. The study draws on literature from the “new sociology of childhood” and applies Bronfenbrenner’s social-ecological model to an analysis of young people’s experiences when their mobility outside the home was restricted, and they were forced to reorganise their time use. The findings show how the pandemic extended the social contexts in which children and their families are embedded and highlighted the role played by socio-cultural factors in shaping children’s coping capacities. In combination, analysis of the two datasets demonstrated the differential effects of lockdown on young children. The accounts from the first wave of the pandemic in 2020 suggested that positive family environments could smooth the negative effects of lockdown and help them cope with unexpected changes in their everyday lives. The interviews during the second outbreak of the pandemic revealed how the emerging weariness and boredom reported by some children strained family relationships. The amount of time that children spent on the web both modified and expanded their experiences of technology-supported interactive spaces. Their reports showed that the interactive contexts in which they were operating through social media, extended beyond national borders to an interest in transnational and global events. Online communication did not, however, compensate for the loss of real-life contacts with friends, which became a major concern for young people in Estonia. In the concluding discussion, the authors consider policy responses that address the main issues identified in the research.